Jihad melawan korupsi - Dharmawan, HCB; Rosari, Al Soni BL de (Jakarta : Penerbit Buku Kompas, 2005)
Issues on law enforcement against corruption in Indonesia; collection of articles
Daftar penulis : p. 258-260
Keywords: Islam and politics -- Indonesia; Political corruption -- Indonesia; Jihad -- Indonesia; Indonesia -- Politics and government